The Influence of Medical Insurance on Patient Access to Orthopaedic Surgery Sports Medicine Appointments Under the Affordable Care Act. Issue 7 (7th July 2017) - Wiznia, Daniel H.; Nwachuku, Emmanuel; Roth, Alexander; Kim, Chang-Yeon; Save, Ameya; Anandasivam, Nidharshan S.; Medvecky, Michael; Pelker, Richard
Background: The goal of the Patient Protection and Affordable Care Act (PPACA) was to expand patient access to health care. Since the rollout of the PPACA, Medicaid patients have demonstrated difficulty obtaining appointments in some specialty care settings. Purpose: To assess the effect of insurance type (Medicaid and private) on patient access to orthopaedic surgery sports medicine specialists for a semiurgent evaluation of a likely operative bucket-handle meniscus tear. The study was designed to determine whether disparities in access exist since the PPACA rollout. Study Design: Cohort study; Level of evidence, 2. Methods: The design was to call 180 orthopaedic surgery sports medicine specialists in 6 representative states (California, Ohio, New York, Florida, Texas, and North Carolina) between June 2015 and December 2015. An appointment was requested for the caller's fictitious 25-year-old-brother who had suffered a bucket-handle meniscus tear. Each office was called twice to assess the ease of obtaining an appointment: once for patients with Medicaid and once for patients with private insurance. For each call, data pertaining to whether an appointment was given, wait times, and barriers to receiving an appointment were recorded. Results: A total of 177 surgeons were called within the study period. Overall, 27.1% of offices scheduled an appointment for a patient with Medicaid, compared with 91.2% ( P < .0001) for a patient with private insurance. Medicaid patients were significantly more likely to be denied an appointment due to lack of referral compared with private patients (40.2% vs 3.7%, P < .0001), and Medicaid patients were more likely to experience longer wait times for an appointment (15 vs 12 days, P < .029). No significant differences were found in patients' access to orthopaedic surgery sports medicine specialists between Medicaid-expanded and -nonexpanded states. Medicaid reimbursement for knee arthroscopy with meniscus repair was not significantly correlated with appointment success rate or patient waiting periods. Conclusion: Despite the passage of the PPACA, patients with Medicaid have reduced access to care. In addition, patients with Medicaid confront more barriers to receiving appointments than patients with private insurance and wait longer for an appointment.